Thread Wire Head Size Detection System Based on ZYNQ. Issue 1 (1st September 2022) - He, Zongfeng; Ma, Xiaocheng; Zhang, Kai; Xiao, Jian
Abstract: Aiming at the problems of slow detection speed and low integration of machine vision threaded wire head, this paper designs a threaded wire head size detection system on the ZYNQ (FPGA+ARM) platform based on the idea of software and hardware collaborative design. First, the functions of image data acquisition, image preprocessing and edge detection are realized on the FPGA side; then the processed data is transferred to the ARM side through VDMA, and the current frame image in the DDR is intercepted by external triggering; finally, the PS side is designed Feature point screening and size calculation algorithms. The experimental results show that the parameter measurement error of this system is small, and it can meet the task requirements of the size detection of the threaded steel wire head.